Career Decision Making Process among High School Students (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
Career decision making is one of the key aspects that professionals in career guidance are interested in assessing. Career decision making process is strongly coupled with society expectations of certain chosen career paths and a strong belief that many should pursue these careers.  This paper focused on how students utilize career counseling services for decision making in higher Schools in Nigeria. Thirty-four public high schools were selected. 380 students of Senior Secondary Schools (SS3A) were randomly selected. Descriptive statistics was used to find the mean and the standard deviation of the respondents. The findings show that students utilize career counseling for decision making. To a large extent utilization of career counseling is highly effective for students career decision making process.